Prevalence, Correlates, and Public Health Implications of Mental Disorders in Uzbekistan and Indonesia: A Systematic Review - Sardorbek Ibragimov; Sinthia Nurhabibah; Muhammad Hisyam Syafii; Dzaka Ogan Amirudin Lutfi (Epidemiology and Society Health Review (ESHR), 2026)
Background: Mental disorders represent a growing public health challenge in low- and middle-income countries. This study aimed to comparatively investigate the prevalence, sociodemographic correlates, and public health implications of mental disorders in Uzbekistan and Indonesia, two lower-middle-income nations sharing structural mental health system challenges despite differing geographic and cultural contexts. Methods: A comparative epidemiological study was conducted using secondary data from publicly available sources, including the World Health Organization, Global Burden of Disease database, Indonesian national health surveys, the Uzbekistan Ministry of Health, and Scopus-indexed literature (2013–2024). No primary data were collected. Results: Indonesia reports that 14.7% of adults experience anxiety and depression symptoms, yet most remain untreated despite an annual economic burden of USD 29.22 billion. Uzbekistan lacks national prevalence data, with mental health services heavily reliant on inpatient care and a limited psychiatric workforce. Both countries face substantial treatment gaps, workforce shortages, and slow progress in deinstitutionalization. Conclusion: Both countries face substantial unmet mental health burdens requiring urgent investment in community-based care, workforce expansion, primary care integration, and evidence-based policy implementation to reduce treatment gaps and improve population mental health outcomes.